1995
DOI: 10.1093/chemse/20.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical and Autonomic Alteration by Administration of a Pleasant and an Unpleasant Odor

Abstract: The present study was designed to investigate whether there is a consistent response in ongoing EEG due to repetitive olfactory stimulation. Two odors of different hedonic quality were presented bilaterally to five male subjects at suprathreshold levels. A room-air blank served as the control stimulus. Each odor was presented six times to each subject in each of three sessions. Electrocortical activity, heart rate, skin conductance and breathing cycle were recorded continuously. EEG variables assessed were dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(71 citation statements)
references
References 37 publications
5
61
1
4
Order By: Relevance
“…Moreover, our results support the hypothesis that visual stimulus-induced positive emotions are related with the left cerebral hemisphere (Davidson, 1992(Davidson, , 1982Tomarken et al, 1992). Furthermore, unfavorable odor-stimulated unpleasant emotion appears to incrementally excite bilateral frontal regions of humans (Kim and Watanuki, 2003;Kline et al, 2000;Brauchli, 1995;Van Toller et al, 1993). Taken together, the data from EEG studies render possible assessments of exogenously stimuli to be interpreted as being pleasant or unpleasant by the brain.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, our results support the hypothesis that visual stimulus-induced positive emotions are related with the left cerebral hemisphere (Davidson, 1992(Davidson, , 1982Tomarken et al, 1992). Furthermore, unfavorable odor-stimulated unpleasant emotion appears to incrementally excite bilateral frontal regions of humans (Kim and Watanuki, 2003;Kline et al, 2000;Brauchli, 1995;Van Toller et al, 1993). Taken together, the data from EEG studies render possible assessments of exogenously stimuli to be interpreted as being pleasant or unpleasant by the brain.…”
Section: Discussionsupporting
confidence: 84%
“…6). Brauchli et al (1995) suggested that olfactory stimulation by an unpleasant odor leads to a stronger cortical deactivation than does such stimulation by a pleasant odor. We expected the effects of odors in relation to positive or comfortable feelings.…”
Section: Figmentioning
confidence: 99%
“…Recently, a number of reports on chemosensory evoked or event-related potentials in mammals have appeared [11,34,37,43,44,50,60]. Some of them report increase of theta and/or alpha activity in EEG during odor application.…”
Section: Rele6ance For Comparati6e Studiesmentioning
confidence: 99%